2017
DOI: 10.21767/2574-2825.1000008
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Trust, Interaction, and Empathy in Doctor-Patient Relationship on Patient Satisfaction

Abstract: Objective: This study is designed to explore the impact of trust, interaction and empathy in doctor-patient relationship on patient satisfaction. Method:This study utilizes questionnaires with target patients in Taiwan as the intended respondents. A total of 446 valid questionnaires were collected for relevant analysis using regression models.Results: Trust (t=4.215, p<0.001), interaction (t=4.997, p<0.001) and empathy (t=8.474, p<0.001) have shown significant positive correlation with patient satisfaction (p<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
2
1
0
Order By: Relevance
“…The positive correlation between communication satisfaction and the duration of care under the current physician is in line with previous findings both in the general population ( Chandra et al., 2019 ; Chang et al., 2013 ; Lan and Yan, 2017 ) and in military settings ( Hochman et al., 2008 ), confirming the importance of the relationship. From the current results, it appears that Iraqi physicians are either consciously or unconsciously inclined to pay attention to interpersonal dynamics and factors such as rapport, compassion, genuineness, respect, and privacy.…”
Section: Discussionsupporting
confidence: 90%
“…The positive correlation between communication satisfaction and the duration of care under the current physician is in line with previous findings both in the general population ( Chandra et al., 2019 ; Chang et al., 2013 ; Lan and Yan, 2017 ) and in military settings ( Hochman et al., 2008 ), confirming the importance of the relationship. From the current results, it appears that Iraqi physicians are either consciously or unconsciously inclined to pay attention to interpersonal dynamics and factors such as rapport, compassion, genuineness, respect, and privacy.…”
Section: Discussionsupporting
confidence: 90%
“…Likewise, this result is consistent with a study which was done in the United States, the study revealed that shorter time in waiting for care was associated with enhancing and improved satisfaction rates [29].The present study reported that the patients' trust in doctors who had chances to be fully satisfied with health care system. This finding is similar to an earlier study done by [30] displayed that patient empathy and trust was a positive correlation with patient satisfaction. Also, the result of the study in line with the study done by [31] who reports that patients completely influenced their satisfaction in coronary angiography care by experience and confidence among the health care providers.…”
supporting
confidence: 92%
“…This finding is similar to previous studies done (14, 4143). A study conducted by Lan et al in Taiwan showed that together with interaction and empathy, trust was positively correlated with patient satisfaction (13). Chang et al in their study also showed that perception of trust among patients positively influenced their satisfaction (14).…”
Section: Discussionmentioning
confidence: 99%